How story-based videogame develops English vocabulary of EFL college students - Priasmoro, Baruna; Priyatmojo, Arif Suryo (ELT Forum: Journal of English Language Teaching, 2025)
This article aims to analyze how the role of video games on English vocabulary language learning among English as Foreign Language college students at university. It explains because the nature of story-based videogames, story-based videogames use scene and dialogues, are often interesting for player who like story, and are part of modern culture, there are lots and lots way to remember and learn words that are used in daily communications. This conceptual article explains a simple concept or a plan pointing how to use story-based videogames can help college students improve and comprehend vocabulary better, memorize them, and applying or using them more effectively and practically. The concept shows how important that is to use the resources from digital device to make learning more exciting, efficient and engaging. In the end of discussion there is suggestion how to develop vocabulary or language skill, we don’t have to stick on traditional ways; we can also use media or use online learning or even both of them. And one of many ways to develop vocabulary or language skill is by using story-based videogames. However, it is important to remember that we cannot rely on videogames alone; It is better to use story-based videogames as complementary tools.